Book review: "Not either an experimental doll" - Eagle, Gillian (PINS-Psychology in Society, 2025)
Marks, Shula, (1987). Not Either an Experimental Doll. Durban and Pietermaritzburg, Killie Campbell Africana Library and University of Natal Press. Pp. 217 ISBN: 087980 542 8 R17.95 One could well question of what relevance a review of a history book is to a psychology journal. However, Shula Marks' "Not Either an Experimental Doll" is an unusual and multi-dimensional documentation of the correspondence of three women which, offers a fascinating insight into the personalities and relationships between these three central figures.